2016
DOI: 10.1089/jop.2015.0088
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Melphalan After Intravitreal Injection in a Rabbit Model

Abstract: Intravitreal administration of 15 μg melphalan leads to pharmacological vitreous levels with low aqueous exposure. Melphalan concentrations in the retina were measurable up to 12 h after dosing, but we report nondetectable systemic exposure in the rabbit. The results correlate with the clinical features of retinoblastoma patients that show control of vitreous seeds without systemic toxicity using intravitreal melphalan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Aqueous seeding has remained an intractable form of retinoblastoma due to a sanctuary effect linked to insufficient drug bioavailability in the AC, despite direct ophthalmic artery or intravitreal delivery, to achieve an antitumor effect [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Aqueous seeding has remained an intractable form of retinoblastoma due to a sanctuary effect linked to insufficient drug bioavailability in the AC, despite direct ophthalmic artery or intravitreal delivery, to achieve an antitumor effect [11]. …”
Section: Discussionmentioning
confidence: 99%
“…By localizing the chemotherapy, P-IVitC restricts the effective V d , as melphalan can only diffuse so far before rendered inactive by its short 1-h half-life [15]. Willekens et al [16] investigated intravitreal dispersion of iomeprol, a water-soluble contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming comparable melphalan diffusion, a P-IVitC dose of just 3.5 µg melphalan could theoretically reach the 4.0 μg/mL tumoricidal concentration around target vitreous seed(s) (0.9 mL accessible vitreous × 4.0 μg/mL tumoricidal concentration = 3.5 µg dose). The effects of diffusion past 1 h could be clinically insignificant, owing to the short 1-h half-life of melphalan and increase in globe movements as the child awakens from anesthesia [15]. A 75% dose reduction to 3.5 µg would likely reduce retinal toxicity, but its effectiveness in seed control would need to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, IVT injection of melphalan or topotecan has also shown promise as a means of eradicating vitreous seeding of retinoblastoma with acceptable side effects [8]. A recent paper demonstrated that after an IVT injection of melphalan in a rabbit eye, the concentrations of the drug in the vitreous and anterior chamber were, respectively, 7.8 and 0.024 µg/mL, with a rapid clearance of the drug in the anterior chamber [9]. This pharmacokinetic study showed that in case of anterior chamber involvement, IVT injection alone is probably not sufficient.…”
Section: Discussionmentioning
confidence: 99%